Transfer pricing risk awareness of multinational corporations: Evidence from a global survey - Sven P. Jost (University of Salzburg, Department of Social Sciences and Economics, 2009)
This paper investigates the transfer pricing risk awareness of multinational firms using cross-sectional data of more than 350 firms located in 24 countries and classified in 12 industries. Moving beyond the sole tax optimization motives of multinational firms, we extend the existing literature by using unique firm-level information such as that the transfer pricing risk awareness is assessed and reported by the person ultimately responsible for transfer pricing. We find that the level of transfer pricing risk awareness of multinational companies predominantly depends on (i) the industry a firm operates in, (ii) a country's risk classification with respect to its transfer pricing regulations (e.g., penalty regimes in case of non-compliance with transfer pricing regulations), (iii) firm size and (iv) the interaction effect of the first two factors. By way of contrast, the time of introduction of transfer pricing regulations and also tax considerations do not seem to play a crucial role for transfer pricing risk perceptions.
Keywords: F23; H25; 330; Transfer pricing; International taxation; Multinational firms; Tax risk management